Effect of freeze-pressure regulated extraction technology on the physicochemical properties and pharmacological activities of guizhi extract - Zhang, Huiling; Luo, Juanzhen; Wan, Qinzhao; Wang, Xuecheng; Wu, Zhenfeng; Yang, Ming; Wang, Yaqi (Frontiers in Chemistry, 2025)
Extraction is the core process for obtaining bioactive compounds from medicinal plants. Enhancing the extraction efficiency of aromatic herbs has become a critical challenge. This study introduced a novel freeze-pressure regulated extraction (FE) technique to improve the extraction efficiency of Gui Zhi (GZ). Compared to traditional methods, FE yielded a significantly lower pH of 4.74, a higher zeta potential of −13.93 mV, and a smaller average particle size of 304.57 nm. Scanning electron microscopy (SEM) and mercury intrusion porosimetry (MIP) confirmed that FE creates larger pores and an expanded surface area, facilitating more effective compound release. HPLC analysis indicated that FE increased the cinnamaldehyde content from 348.53 to 370.20 μg/g. UPLC-MS analysis further demonstrated that FE is more effective for extracting volatile and phenolic compounds. Furthermore, the therapeutic effect of GZ extract on a wind-cold syndrome model was investigated. FE significantly alleviated symptoms and restored lung tissue integrity, through the regulation of the citric acid cycle and thiamine metabolism pathways. The findings not only support the application of FE technology in herbal extraction but also offer novel approaches for the efficient utilization of herbs like GZ in modern medicine.